Plate on Plate Osteosynthesis for the Treatment of Nonhealed Periplate Fractures. (11th March 2014) - Arealis, Georgios; Nikolaou, Vassilios S.; Lacon, Andrew; Ashwood, Neil; Hamlet, Mark
Abstract : Purpose. The purpose of this paper is to present our technique for the treatment of periplate fractures. Methods. From 2009 to 2012 we treated three patients. In all cases the existing plate was left and the new one placed over the existing. Locking screws were placed through both plates. The other screws in the new plate were used as best suited the fracture. Results. In all cases less than 6 months had passed between fractures. None of the original fractures had healed. Mean followup was 2 years. All fractures proceeded to union within 7 months. No complications were recorded. All the patients returned to their normal activities and were satisfied with the results of their treatment. Conclusion. Our plate on plate technique is effective for the treatment of periplate fractures. A solid fusion can be achieved at the new fracture site without disturbing the previous fixation.